Optimising Social Studies Learning Through the Use of Simple Candy Reward to Boost Student Participation and Motivation at SDN 4 Baubau - Suarti Suarti; Yurfiah; Kosilah; Dina Komalasari; Faslia; Wa Ode Rikiti (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This study aims to examine the implementation of a simple reward in the form of candy to enhance students' motivation and participation in Social Studies learning. In the learning process, students' motivation and participation are essential factors that determine learning success. Therefore, teachers are required to create an engaging and enjoyable learning environment that encourages students to participate actively in classroom activities. One simple strategy that can be applied is providing candy as a reward to students who demonstrate active participation, discipline, and the ability to answer the teacher's questions. This study employed a descriptive qualitative approach using observation, interviews, and documentation as data collection techniques. The findings indicate that providing candy as a simple reward effectively increases students' enthusiasm, encourages them to ask and answer questions more actively, and creates a more enjoyable classroom atmosphere. Furthermore, students become more motivated to pay attention to the teacher's explanations and participate actively in Social Studies learning activities. Therefore, a simple reward system can serve as an effective instructional strategy when implemented appropriately and without excessive use.